From Flash in the Pan to Continuous Ban: How the Power of Theory of Planned Behavior in Continuous Boycott Intention - Sarah Awliya Dini; Rifelly Dewi Astuti (Cita Konsultindo Research Center, 2024)
This study aims to analyze the role of Theory of Planned Behavior (TPB) and religiosity in influencing Continuous Boycott Intention toward Israeli-affiliated fast-food restaurants, in Indonesia. Utilizing the statistical analysis method of Structural Equation Modeling - Partial Least Squares (SEM-PLS), this study involved 400 respondents to test the validity of previously formulated hypotheses. The research results showed that (1) Religious Animosity and Perceived Success Likelihood have a significant positive impact on Attitude toward Boycott; (2) Attitude toward Boycott and Perceived Behavioral Control of Boycott have a significant positive impact on Continuous Boycott Intention, while Brand Loyalty has a significant negative impact on Continuous Boycott Intention; (3) Subjective Norm on Boycott and Motivation to Comply have a non-significant positive impact on Continuous Boycott Intention. Data was obtained from an independent survey with an online questionnaire, then analyzed through Wording Test, Pre-Test, and Main Test. The results of the analysis showed that all variables had good validity and reliability.